Functional and taxonomic biogeography of phytoplankton and zooplankton communities in relation to environmental variation across the contiguous USA. (19th February 2020) - Sodré, Elder De Oliveira; Langlais-Bourassa, Alexandre; Pollard, Amina I; Beisner, Beatrix E
Abstract: For biomonitoring of aquatic ecosystems, the use of coarse group classifications, either taxonomic or functional, has been proposed as an alternative to more highly resolved taxonomic identification. We tested this proposition for phytoplankton and zooplankton using a pan-United States dataset, which also allows us to investigate biogeographic relationships between plankton groups and environmental variables. We used data from 1010 lakes composing the 2012 US National Lakes Assessment and compared relationships derived using genus-level, more aggregated taxonomic resolution and functional types. We examined responses nationally and by ecoregion. Differences in plankton assemblages among ecoregions were detected, especially at genus-level classification. Our analyses show a gradient of altitude and temperature influencing both phytoplankton and zooplankton, and another gradient of nutrients and anthropogenic activity influencing mostly phytoplankton. The overall variation in the planktonic communities explained by environmental variables ranged from 4 to 22%, but together indicated that aggregated taxonomic classification performed better for phytoplankton; for zooplankton, the performance of different classification types depended on the ecoregion. Our analyses also revealed linkages between particular phytoplankton and zooplankton groups, mainly attributable to similar environmental responses and trophic interactions. Overall, the results support the applicability of coarse classifications to infer general responses of plankton communities to environmental drivers.